Outcome in kidney transplant recipients receiving kidneys from renal donors screened using 51CR-EDTA to determine glomerular filtration rate - Malan, Nico (My University, 2014)
There is a global preponderance of renal disease and many of these conditions are associated with renal failure. A significant proportion of these patients will develop advanced kidney disease with ultimately end stage renal failure. Kidney transplantation is the most successful treatment of patients in end stage renal failure. Currently, the majority of transplantations in the University of the Witwatersrand (WITS) Academic complex (which comprises Charlotte Maxeke Academic, Helen Joseph and Chris Hani Baragwanath Academic Hospitals) are performed with cadaveric donor kidneys. With the worldwide shortage of kidneys required for patients in renal failure, living kidney donation has increased the availability of donor kidneys. Potential renal donors (PRD) are subjected to a battery of investigations prior to being considered for donation, amongst other, glomerular filtration rate (GFR). Potential renal donors at the WITS Academic Complex undergo GFR assessment using 51Cr-ethylene-diamine-tetra-acetic acid (EDTA). Some PRD, potentially those on a vegetarian diet, have a “low” GFR (≤80ml/min/1.73m2) and do not meet criteria for renal donation. These potential renal donors are requested to follow a novel protocol, following a diet high in animal protein (beef and fish) for one week after which time the GFR is determined again. Potential renal donors where the GFR increases (thus showing good renal reserve), subsequently donate a kidney. We do not know the outcome of recipients receiving kidneys in which the GFR “normalized” following a protein load. To the best of our knowledge, the outcome of such recipients is also not described in the current available body of literature. The aim is to determine the outcome in recipients receiving kidneys from protein loaded donors versus recipients of non-protein loaded (“normal” GFR) kidneys. Methods The study follows a retrospective record analysis of patient demographics and work-up results (cross-matching, GFR, infectious diseases, renal anatomy etc.) and outcomes in: i. All potential renal donors (PRDs) from 1997 to July 2012 who had GFR determined by clearance of 51Cr-EDTA ii. The subset of those who donated a kidney iii. Donors with “low” (≤80ml/min/1.73m2) baseline GFR and subsequent protein-loaded GFR iv. Donors with a “normal” (>80ml/min/1.73m2) GFR v. The recipients receiving the grafts – outcome, complications, creatinine over time and survival Results In this study it was shown that 51Cr-EDTA clearance correlates with calculated creatinine clearance (r2=0.44) within the range of 51Cr-EDTA clearance between 40 and 180ml/min (uncorrected for BSA). It was also shown that reproducibility of 51Cr-EDTA clearance in 7 donor patients was excellent (r2=0.86), suggesting a robust method. Two hundred and forty nine patients were screened using 51Cr-EDTA clearance. Two hundred and twelve potential donors had good GFR and were not protein loaded. Of these potential renal donors, one hundred and twenty four were well matched and donated to recipients, with complete follow up in 85 cases. A total of 88 potential donors were excluded for various reasons. In this non-protein loaded group that donated kidneys, overall graft and recipient survival over 16 years was 64%. Thirty seven potential renal donors were protein loaded since their initial GFR was ≤80ml/min/1.73m2. Of these 37 potential donors, 15 were excluded. Twenty two potential donors donated kidneys in this group, with outcomes available in 13 recipients. Overall graft and recipient survival over 14 years was 58.3% for this group. This was not significantly different from the recipients receiving grafts from non-protein loaded donors (p=0.14; log rank test). For potential donors, upon protein loading, GFR increased significantly to 89.3±18.4 ml/min/1.73m2 (p<0.0001), with a mean percentage increase of 26.0±24.4% (median 22.2%; range: -12.9% to +103.4%). Furthermore, when comparing only patient survival between recipients of grafts from donors that were protein loaded and donors that were not protein loaded, there is still no significant difference between the two groups. The pre-protein loaded GFR correlated with the post-protein loaded GFR measurement. There was a negative correlation between pre-protein load (baseline) GFR and percentage increase in GFR following protein loading. In all donors, GFR declined from pre-transplant determination of 97.7±18.1ml/ min/1.73m2 to 75.2±16.4ml/min/1.73m2 (p<0.005). Discussion and conclusion 51Cr-EDTA is a reliable, reproducible technique to assess the GFR of potential renal donors. The novel protein loading technique developed in our institution is a convenient way to assess the functional renal reserve of potential renal donors that have a suboptimal estimated GFR of ≤80ml/min/1.73m2. Although the patient numbers in this study are small, there is no significant difference between the outcome of recipients of renal grafts from non-protein loaded and protein loaded donors. The inclusion of potential donors that show a normal GFR post protein load may increase the pool of available kidney grafts and assist greatly in the treatment of many patients with end stage renal disease. Further research in this area is encouraged, and multicenter studies may yield results that with larger number of patients that may ratify the results of this study.